Recovery of Waste Materials: Technological Research and Industrial Scale-Up - Medici, Franco (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Increases in population, booming economy, rapid urbanization and the rise of living standard have exponentially accelerated waste production. Currently, 2 billion tons per year of municipal solid waste is produced worldwide and about 33% of this amount remains uncollected by different municipalities.. However, the entire waste production process concerns different streams and origins other than municipal solid waste, including industrial, agricultural, construction and demolitions waste; and hazardous, medical and electronic waste. Published papers, as a whole, concern different waste materials such as the recovery of different building materials, the treatment of waste deriving from electrical and electronic equipment, the utilization of stainless-steel slags, agricultural and domestic waste and plastics. In conclusion, the works demonstrate scientific and technological relevance in terms of the topics dealt with, but the problems addressed in this Special Issue proceed beyond the solution that the scientific community is able to propose. In fact, our industrial system, at the end of its cycle of production and consumption, has not developed the capacity to absorb and reuse waste and byproducts. We have not yet managed to adopt a circular model of production capable of preserving resources for present and future generations.